THE USE OF DIGITAL TECHNOLOGIES IN DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE IN ENGLISH LANGUAGE TEACHING - Berdiqulova Mahbuba Erkinon qizi; Tolipova Nilufar Jaxongir qizi (TADQIQOTLAR, 2026)
ABSTRACT This article examines the role of digital technologies in developing students’ communicative competence in the process of teaching English in higher education institutions. The study analyzes the impact of modern digital tools, including multimedia resources, online platforms, and interactive applications, on improving students’ speaking, listening, reading, and writing skills. Special attention is paid to the importance of digital technologies in increasing students’ motivation, independent learning abilities, and active participation in the educational process. The article also identifies existing problems related to the use of digital technologies, such as insufficient digital competence of teachers and technical limitations. Based on the analysis of scientific literature and pedagogical practice, practical recommendations are proposed for the effective integration of digital technologies into English language teaching. The results show that the use of digital technologies contributes to improving the quality of education and the development of students’ communicative competence.